2006
DOI: 10.5172/conu.2006.21.2.186
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence, health and health care: Women’s accounts of their experiences

Abstract: The current health service response to women's domestic violence related health issues seeks to categorise their presenting symptoms into physical and psychological ailments This gives a narrow and somewhat simplistic focus to what is a complex phenomenon and may obscure women's experiences and limit the opportunities to provide proactive health care. The purpose of this study was to expand knowledge about the health issues of women who are subjected to domestic violence, by affording primacy to women's accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 1 publication
0
35
0
Order By: Relevance
“…Several studies conclude that health care providers are less likely to screen for domestic violence when they believe that screening is not within their professional role-that is, not a medical problem (Coker, Bethea, Smith, Fadden, & Brand, 2002;Jaffe, Epling, Grant, Ghandour, & Callendar, 2005;Spangaro, Poulos, & Zwi, 2011). Therefore, it is not at all surprising that, according to several studies, victims of domestic violence have not considered the help they have received from health care professionals to be very useful (Bacchus et al, 2003;Macy, Johns, Rizo, Martin, & Giattina, 2011;Peckover, 2003;Tower, McMurray, Rowe, & Wallis, 2006).…”
mentioning
confidence: 89%
“…Several studies conclude that health care providers are less likely to screen for domestic violence when they believe that screening is not within their professional role-that is, not a medical problem (Coker, Bethea, Smith, Fadden, & Brand, 2002;Jaffe, Epling, Grant, Ghandour, & Callendar, 2005;Spangaro, Poulos, & Zwi, 2011). Therefore, it is not at all surprising that, according to several studies, victims of domestic violence have not considered the help they have received from health care professionals to be very useful (Bacchus et al, 2003;Macy, Johns, Rizo, Martin, & Giattina, 2011;Peckover, 2003;Tower, McMurray, Rowe, & Wallis, 2006).…”
mentioning
confidence: 89%
“…[11][12][13][14][15][16][17][18][19] Possible harms or unintended consequences of clinical assessment have been raised and considered in research trials, but thus far no evidence of such harm has emerged. [19][20][21] Barriers for implementation of IPV screening and counseling are myriad, including clinician concerns about time; limited incentives for screening 22 ; either nonexistent or poorly implemented policies to guide clinicians and practices in conducting screening; lack of knowledge and confidence about how to support a patient who discloses IPV, [23][24][25][26][27] which may reflect lack of reliable intervention services 28 ; and inadequate crosssector collaborations with victim service advocates. 29,30 Addressing barriers and improving screening, counseling, and referral practices require attention to multiple levels within the healthcare delivery system to create a safe, trusting environment for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that when health care practitioners screen for IPV, women are more likely to access resources such as shelter and counseling services, and they have more positive health outcomes (McCloskey et al, 2006). Failure to screen for IPV followed by appropriate intervention, however, may further adversely affect the health of the women experiencing IPV (Tower, McMurray, Rowe, & Wallis, 2006). In this light, many medical associations (e.g., American Medical Association [AMA], American College of Obstetricians and Gynecologists [ACOG],and American Academy of Family Physicians) and researchers have recommended that health care providers ask patients about IPV and provide appropriate treatment and referrals when IPV is identified (Brown, 2002).…”
Section: We Explored How Korean American (Ka) Physicians In the Los Amentioning
confidence: 96%